2012
DOI: 10.5923/j.mining.20120101.01
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Novel Techniques for Chalcopyrite Ore Processing

Abstract: Chalcopyrite ores are usually processed by means of hydrometallurg ical or pyro metallurgical processes, but due to environmental aspects and the possibility of increased exp loitation of mixed and lower grade ores and relat ively small isolated deposits, there has been a worldwide upsurge of interest in the hydrometallurg ical processes of this ore as compared to pyrometallurgy. The different concentrates obtained through differential flotation in pyro metallu rgy are usually of poor quality with low metal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 40 publications
0
36
0
1
Order By: Relevance
“…Industrial scale leaching of copper sulfide minerals like chalcopyrite (CuFeS 2 ) remains a metallurgical challenge. Chalcopyrite is mined worldwide [1], given the depths at which mining operations can now be carried out [2]. Copper sulfide is extracted by flotation, followed by the application of pyrometallurgical methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial scale leaching of copper sulfide minerals like chalcopyrite (CuFeS 2 ) remains a metallurgical challenge. Chalcopyrite is mined worldwide [1], given the depths at which mining operations can now be carried out [2]. Copper sulfide is extracted by flotation, followed by the application of pyrometallurgical methods [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrometallurgy, which involves solution-based extractive techniques such as heap leaching and bioleaching, is considered a viable alternative to pyrometallurgy due to lower startup and operational costs [5,6]. Furthermore, with no harmful gas emissions, hydrometallurgy is less environmentally hazardous than pyrometallurgy, although care must be taken to ensure stabilization of the final leaching residue prior to disposal [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies related to the development of hydrometallurgical routes to extract copper from low-grade sulfide ores by atmospheric leaching and biological leaching processes [15][16][17][18] . Authors have concluded that both direct atmospheric and biological leaching of copper from its ore are extremely slow due to the formation of an elemental sulfur passivation layer on the surface of unreacted particles 3 . On the other hand, huge amounts of acid are required in the copper leaching from the low-grade copper ore, especially it contains large amounts of carbonates or siliceous gangue minerals as impurities which make difficulty on the separation process and produce many residues.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcopyrite (CuFeS 2 ) is the most abundant and the most refractory copper sulfide mineral which accounts for about 70% of the copper reserves in the world 2 . At present, a large portion of the copper is produced from chalcopyrite ore via flotation followed by the pyrometallurgical method [3][4][5] . Due to the long-term mining activity and economic growth of countries in the world, the reduction of copper grade and depletion of high-grade copper ore have gradually been happened during last several decades 6,7 .…”
Section: Introductionmentioning
confidence: 99%